Impacts of transport strike on Pakistan economy: An inoperability Input-Output model (IIOM) approach. (December 2021) - Ali, Yousaf; Bilal, Muhammad; Sabir, Muhammad
Abstract: The transport sector has backward and forward linkages with other sectors of the economy. A strike in the transport sector can be disruptive for other interdependent sectors of the economy. This study investigates the macroeconomic impacts of a transportation strike using the Inoperability Input-Output (IIOM) model. The study uses 25 sectors Input-Output tables of Pakistan economy and combines IIOM approach with Monte Carlo Simulations to quantifies the impacts of 21 days (during 2012) transport strike on Pakistan economy. The results indicate that the most affected sector of that strike was financial intermediation sector followed by the food & beverages sector and petroleum, chemical & non-metallic mineral products sector being the second and third most affected sectors, respectively. The study is an application of IIOM in transportation strikes and has usefulness for the policymakers, researchers, and readers that has an interest in application and extensions of Input-Output based analysis. Highlights: Transport sector works as a backbone in the economy due to its backward and forward linkages with other sectors of the economy. There is hardly any scholarly work based on developing countries that do study the impacts of transport strikes on the economy. This research uses Inoperability Input-Output Model (IIOM) to study the impacts of transport strike on the Pakistan economy. The study is useful for policymakers and researchers having an interest in the quantification of the impact of transport strike at the macroeconomic level.